Prototype development of micro hydropower house - Dee, Seng Cheang (Universiti Malaysia Perlis (UniMAP), 2012)
Due to the fact that the cost of oil, gas and electricity is increasing, the engineers are urged to find alternative sources of energy. Another reason, which urges them to do so is to reduce the impacts of the environment. The main objective in this project is to construct a micro hydropower house that can produce electricity to a small bulb. This project report summarize on how to design and construct a micro hydropower house that can produce the electricity. The hydropower plant uses inexpensive components and used components for construction. The waterwheel turbine is well suited for the prototype development of micro-hydropower house. This prototype consists of a 12Volt motor which is used as a DC generator, turbine case and drive system. The DC generator driven by a waterwheel turbine is connected to the faucet. The maximum power generated by the micro hydropower house is 2.5Watt. Consequently, this prototype was developed successfully and able to lighten a small bulb which has met the main objective of the project. Such prototype development shall be very useful for the human in the coming future for small power consumption.